2022
DOI: 10.3390/ijms231810408
|View full text |Cite
|
Sign up to set email alerts
|

Colitis Induces Sex-Specific Intestinal Transcriptomic Responses in Mice

Abstract: There are significant sex differences in colorectal cancer (CRC), including in incidence, onset, and molecular characteristics. Further, while inflammatory bowel disease (IBD) is a risk factor for CRC in both sexes, men with IBD have a 60% higher risk of developing CRC compared to women. In this study, we investigated sex differences during colitis-associated CRC (CAC) using a chemically induced CAC mouse model. The mice were treated with azoxymethane (AOM) and dextran sodium sulfate (DSS) and followed for 9 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…It is known that there are sex-dependent differences in response to glucocorticoids. Recently, a study observed an overrepresentation of transcriptomic targets of the glucocorticoid receptor pathway in DSS colitis [ 27 ]. It is known that females exert more potent pro-inflammatory processes due to significantly higher estrogen liberation and a lower presence of androgens than males, these being pro-inflammatory and anti-inflammatory, respectively [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that there are sex-dependent differences in response to glucocorticoids. Recently, a study observed an overrepresentation of transcriptomic targets of the glucocorticoid receptor pathway in DSS colitis [ 27 ]. It is known that females exert more potent pro-inflammatory processes due to significantly higher estrogen liberation and a lower presence of androgens than males, these being pro-inflammatory and anti-inflammatory, respectively [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, resveratrol, which interacts with estrogen receptors, showed response discrepancies between both sexes in DSS models [ 25 ]. In addition, sex-dependent immune features have been found to be unique for each sex in these models [ 27 , 28 ]. Nonetheless, 64% of the preclinical studies with chemically induced colitis models developed so far used only male animals, 21% used females, and only 4% used both sexes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on IBD-induced taste dysfunction may lack consensus because of the inclusion of patients with both Crohn's disease and ulcerative colitis, patients in different stages of are-up and remission, varied dietary and environmental conditions, sex differences and the use of different methods to test taste sensitivity 1,2,7,8,10-13 . In the current chronic study, we used male mice because acute disease symptoms were more pronounced, likely due to more robust in ammatory responses and protective effects of estrogen in the DSS model 31,35 . Additional studies will determine whether female mice with colitis exhibit similar changes in sweet and umami taste function.…”
Section: Discussionmentioning
confidence: 99%
“…A single dose of intracolonic 2, 4, 6-trinitrobenzenesulfonic acid (TNBS) installation induces colitis in both sexes on day 3 with male mice more severe than female mice [51] and by day 7 colonic hypersensitivity is more pronounced in male mice than in female mice, which is mediated by Piezo2 in nociceptive neurons [24]. Similarly, dextran sodium sulfate (DSS) treatment to induce colonic inflammation affects male mice stronger than female mice showing less inflammatory infiltrates, less crypt damage, and lower TNFα production in the colon of female mice than male mice [52], with sex-differential changes in the immune responses in the colon [53]. Histamine enema increases visceral hypersensitivity in male mice but not female mice and deletion of histamine N-methyltransferase (HNMT) from enteric glia protects males from histamine-driven visceral hypersensitivity, with no effects on female mice [54].…”
Section: Visceral Pain Preclinical Models With Sexual Dimorphismmentioning
confidence: 99%